Localization of the 1, 25-dihydroxyvitamin d-mediated response in the intestines of mice. Issue 186 (February 2019) - Reynolds, Carmen J.; Koszewski, Nicholas J.; Horst, Ronald L.; Beitz, Donald C.; Goff, Jesse P.
Highlights: RNAScope ISH of 1, 25(OH)2 D-stimulated mouse intestines. 1, 25(OH)2 D induces expression of Cyp24a1 mRNA in only epithelial cells of the duodenum and colon. The 1, 25(OH)2 D-mediated response occurs in villi or tips of the intestine rather than crypt regions. An increase in plasma [1, 25(OH)2 D] did not affect the response in the duodenum. Abstract: 1, 25-Dihydroxyvitamin D3 (1, 25(OH)2 D) elicits a transcriptional response in the intestines. Assessments of this response are often derived from crude tissue homogenates and eliminate the ability to discriminate among different cell types. Here, we used an RNA in situ hybridization assay, RNAScope (Advanced Cell Diagnostics, Newark, CA), to identify the cells in the intestine that respond to 1, 25(OH)2 D with expression of cytochrome P450 family 24 subfamily A member 1 (Cyp24a1) mRNA. Mice were gavaged with a single bolus dose of 1, 25(OH)2 D to target the duodenum or a glucuronic acid conjugate of 1, 25(OH)2 D, β-G-1, 25(OH)2 D, to target the colon. QRT-PCR analysis of Cyp24a1 mRNA verified that the 1, 25(OH)2 D-induced responses were present. RNAScope revealed that the mRNA response present after six hours is limited to mature enterocytes exposed to the intestinal lumen in both the duodenum and colon. No detectable expression was observed in goblet cells, lamina propria, muscularis mucosa muscle, submucosa and submucosal lymphoid follicles, or tunica muscularis. Our findings have identified epithelial enterocytes to be the intestinal targets for 1, 25(OH)2 D in both the duodenum and colon.